Occupational social work for the 21st century - Iversen, Roberta Rehner (1998)
Economic restructuring and radical changes in welfare policy are causing increasingly severe employment dislocation and disadvantage among many urban residents, particularly women, members of racial and ethnic minority groups, and youths. Despite the profession's historic commitment to poor people, little advanced social work practice is reported in work-enhancement programs. This article outlines employment-related needs among poor people in the context of economic and policy change. A brief discussion of successful work programs and traditional occupational practice frames the reformulation suggested in the article. Role definitions, settings, and skills needed for expanded occupational social work practice are followed by implications for social work. - Reproduced
Keywords: Social work